Evaluation of miR-216a and miR-217 as potential biomarkers of acute pancreatic injury in rats and mice. (September 2014) - Goodwin, David; Rosenzweig, Barry; Zhang, Jun; Xu, Lin; Stewart, Sharron; Thompson, Karol; Rouse, Rodney
Abstract Mild injury of the exocrine pancreas is often asymptomatic and can be under- or mis-diagnosed. The pancreas-enriched microRNAs miR-216a and miR-217 were evaluated as potential serum biomarkers of exocrine pancreas injury in rodent models of acute pancreatitis induced by caerulein, l-arginine, and pancreatic duct ligation. Both microRNAs showed time- and dose- relevant responses to pancreatic injury and wider dynamic ranges of response than serum amylase or lipase. Pancreas-selective microRNAs were found to be relatively sensitive serum biomarkers of pancreatic injury in rodents with potentially greater specificity than the current standard assays.